KONSEP SERTA SOLUSI PENGEMBANGAN DIRI DALAM ISLAM - Muhammad Alpin Hascan (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
An individual's self-development determines how his or her personality goes forward. Today, many of these individuals do not know the context of self-development in Islam. This article aims to review and discuss the concept of self-development in Islam as well as its development solutions. This research uses qualitative methods with a literature study approach. That is by describing the findings through literature or related scientific journals. Data analysis techniques use content analysis through relevant books as well as scientific references from several appropriate journals. Based on the description of this research, it can be known that the results of the study show that self-development in Islam is something that must be done as a form of gratitude and responsibility as caliph on earth to Allah SWT. In this case, to develop oneself into a better person in Islam is to begin with maintaining the physical body physically and spiritually. Then continue through the process of self-recognition and potential and develop it in order to produce a positive achievement or thing towards better change. In order to develop themselves well, individuals can do several things, namely; Talk about yourself, appreciate time, get out of the safe zone, continue to explore the potential in yourself, the motivation to rise to become a better person and be able to appreciate yourself and others.